Drug Nephrotoxicity in Family Doctor Practice - Violetta Kruczyńska-Kisły; Anna Fabian-Danielewska; Wiesława Fabian (Kazimierz Wielki University, 2019)
Drug Nephrotoxicity is a frequent and growing phenomenon. It is reported that up to 20% of episodes of acute renal failure are due to medication. In the practice of the family doctor, the problem of drug nephrotoxicity is significant. The family physicians are dealing with an aging population of patients with cardiovascular diseases, diabetes, circulatory insufficiency, and pre-existing renal function. This group of patients is subjected to many diagnostic and therapeutic procedures that may worsen the function of kidneys, and often use numerous drugs, and abuse analgesics. Most drugs that cause kidney damage work through such mechanisms: disorder of intra-glomerular hemodynamics, direct damage to the kidney tubules, an inflammatory process, nephropathy associated with the formation of crystals, rhabdomyolysis, thrombotic microangiopathy. Most cases of drug-induced kidney damage are reversible as long as it is diagnosed early and the factor responsible for damage is eliminated.